Phase error analysis of displaced-axis dual reflector antenna for satellite earth stations - Demirci, Aykut; Sonmez, Nurdan; Tokan, Fikret; Tokan, Nurhan Turker (ELSEVIER GMBH, 2019)
In a classical Cassegrain geometry, the sub-reflector partly blocks reflected rays from the main reflector. Feed antenna of the subreflector also blocks some of the radiated energy towards main reflector. In a properly designed displaced-axis dual-reflector antenna (DADRA) system based on axially-displaced ellipse (ADE) sub-reflector configuration, these blockage losses are minimized. Thus, with its high gain and low return-loss, DADRA system is a strong candidate for large scale earth station antennas. In general, to achieve maximum gain using a single-reflector system, the phase center of the feed antenna should be placed at the focus of the paraboloidal reflector. However, phase center of a feed antenna moves with the change of frequency. Phase error loss is not avoidable, especially in wide band applications. In this work, phase error losses due to axial defocusing of a DADRA system designed for satellite earth station are analysed in Ku-band. The system is fed by a corrugated horn. Phase center stability of the feed over a wide frequency band is exhibited resulting in negligible loss levels. The results are compared with that of a single-paraboloidal reflector fed by the same horn. Measured and simulated patterns of DADRA system are presented. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: Corrugated feed horn; Displaced-axis dual reflector; Earth station antennas; Phase error loss; Satellite communication; APERTURE; PERFORMANCE; CASSEGRAIN; Engineering; Telecommunications